Is There a Link between COVID-19 Mortality with Genus, Age, ABO Blood Group Type, and ACE2 Gene Polymorphism? - Hamid CHEGNI; Nafiseh PAKRAVAN; Mojtaba SAADATI; Ali Dalir GHAFFARI; Hadi SHIRZAD; Zuhair M HASSAN (Tehran University of Medical Sciences, 2020)
-